Text‐to‐Haptics: Enhancing Multisensory Storytelling through Emotionally Congruent Midair Haptics - Maciej Stroinski; Kamil Kwarciak; Mateusz Kowalewski; Daria Hemmerling; William Frier; Orestis Georgiou (Advanced Intelligent Systems)
In multisensory storytelling, the integration of touch, sound, speech, and visual elements plays a crucial role in enhancing the narrative immersion and audience engagement. In light of this, this article presents a scalable and intelligent hybrid artificial intelligence (AI) method that uses emotional text analysis for deciding when and what midair haptics to display alongside audiovisual content generated by latent stable diffusion methods. Then, a user study involving 40 participants is described, the results of which suggest that the proposed approach enhances the audience level of engagement as they experience a short AI‐generated multisensory (audio–visual–haptic) story.